1999
DOI: 10.1046/j.1365-3164.1999.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of omega‐3 fatty acid diet enrichment on wound healing

Abstract: Omega‐3 fatty acids were evaluated to determine how their anti‐inflammatory properties affect wound healing. Twelve Beagle dogs were divided into two groups of six. Group I was fed an n‐3 fatty acid enriched diet (n‐3 FAED) with an n‐6 to n‐3 fatty acid ratio of 0.3, and group II was fed a control diet (CD) with a ratio of 7.7. Open and sutured cutaneous wounds were created on the trunk of the dog, and evaluated by laser Doppler perfusion imaging, tensiometry, planimetry, histopathology, and eicosanoid content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…The results of our study confirmed other findings (Scardino et al, 1999;Cardose et al, 2004;Vure and Avinash, 2006) that showed the application of unsaturated fatty acids like linolenic acid (n-3) can increase inflammatory parameters in the first days after surgery and thus, promote the wound healing. On the other hand, several studies have shown that sheep milk contents of unsaturated fatty acids, essential amino acids and important elements like magnesium, calcium, iron, zinc and Bcomplex vitamins, are two or three times more than those of cow milk and indicated the higher therapeutic effects of sheep milk compared to cow milk (Hardy, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study confirmed other findings (Scardino et al, 1999;Cardose et al, 2004;Vure and Avinash, 2006) that showed the application of unsaturated fatty acids like linolenic acid (n-3) can increase inflammatory parameters in the first days after surgery and thus, promote the wound healing. On the other hand, several studies have shown that sheep milk contents of unsaturated fatty acids, essential amino acids and important elements like magnesium, calcium, iron, zinc and Bcomplex vitamins, are two or three times more than those of cow milk and indicated the higher therapeutic effects of sheep milk compared to cow milk (Hardy, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…We used the Abramov's histological scoring system and M. Stacie Scardino study (Abramov et al, 2007;Scardino et al, 2002). Abramov's system assessed each parameter independently and gave it a score of 0-3 (absent=0, Slight=1, moderate=2, extensive=3).…”
Section: Histological Gradingmentioning
confidence: 99%
“…A limited number of studies have examined the effects of dietary or topical applications of PUFA on wound healing. A cutaneous wound healing study found that rats fed a diet enriched in n -3 fatty acids produced wounds that were weaker in tensile strength compared to those from rats fed a diet containing n -6 fatty acids [19]. Cutaneous wounds in dogs fed an n -3 enriched diet had reduced epithelialization and contraction of open wounds and less edema in sutured wounds after 5 days than dogs fed a diet enriched in n -6 fatty acids.…”
Section: Discussionmentioning
confidence: 99%